2001
DOI: 10.1348/096317901167316
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive style on leader‐member exchange: A study of manager‐subordinate dyads

Abstract: The similarity‐attraction paradigm suggests that congruence between the cognitive styles of managers and their subordinates may result in positive leader‐member relationships. A study of 142 manager‐subordinate dyads in two large manufacturing organizations fails to support this idea. Findings suggest, however, that intuitive leaders may be less dominating and more nurturing than their analytic colleagues, and that they are more liked and respected by analytic members than analytic leaders are by intuitive mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 68 publications
1
63
0
2
Order By: Relevance
“…Although there are some disagreements between earlier (Cooper & Miller, 1991;Handley, 1982;Turban & Jones, 1988) and more recent (Allinson et al, 2001;Armstrong et al, 2004;Glomb & Welsh, 2005;KristofBrown et al, 2005) studies on whether similarity of cognitive style will lead to better communication satisfaction or whether a manager with a certain cognitive style will be preferred by all employees regardless of employee cognitive style match or mismatch, or whether a complimentary cognitive style where differences will improve the communication satisfaction, in the high context cultural environment that we conducted our study, we expect that similarity will lead to improved communication satisfaction. Therefore, we hypothesize that:…”
Section: Hypotheses Developmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Although there are some disagreements between earlier (Cooper & Miller, 1991;Handley, 1982;Turban & Jones, 1988) and more recent (Allinson et al, 2001;Armstrong et al, 2004;Glomb & Welsh, 2005;KristofBrown et al, 2005) studies on whether similarity of cognitive style will lead to better communication satisfaction or whether a manager with a certain cognitive style will be preferred by all employees regardless of employee cognitive style match or mismatch, or whether a complimentary cognitive style where differences will improve the communication satisfaction, in the high context cultural environment that we conducted our study, we expect that similarity will lead to improved communication satisfaction. Therefore, we hypothesize that:…”
Section: Hypotheses Developmentmentioning
confidence: 95%
“…There are also some conflicting results in the literature on what happens when the direction of the incongruence is different. Some studies show that analytic managers are preferred even by intuitive followers (Armstrong et al, 2004) whereas others report that intuitive managers are more liked by analytic followers (Allinson et al, 2001).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistent expectation of job responsibilities may negatively affect the relationship between a supervisor and a subordinate [26]. In addition, demographic similarity in a supervisor-subordinate dyad relates to cognitive similarity [26,27]. This suggests that a supervisor-subordinate dyad of the same sex creates a common frame of reference, resulting in increased interpersonal attraction and communication [26].…”
Section: Hypothesesmentioning
confidence: 99%
“…For example, Allinson, Armstrong, and Hayes (2001) investigated the similarity-attraction paradigm in terms of leader-member exchange relationships. They found that the degree of difference between leader and member cognitive styles may influence the nature of the personal relationship or congruence between them.…”
Section: The Attraction Paradigm and The "Similar-to-me" Effectmentioning
confidence: 99%